Implementasi Model Problem Based Learning Berbantuan LKPD pada Materi Asam Basa - Pika Magdalena Naibaho; Marudut Sinaga (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Acid-base learning in high school still tends to be teacher-centered, resulting in low student activity and learning outcomes. This study aims to improve student activity and learning outcomes through the application of the Problem Based Learning (PBL) model assisted by worksheets (LKPD). The study used a quasi-experimental approach with a pretest-posttest control group design. Sixty-four eleventh-grade students were divided into two groups: an experimental class with problem based learning and a control class with direct instruction. The results showed that student learning activities in the PBL class were higher than in the control class. Student learning outcomes in the PBL class also improved significantly compared to the control class. Thus, the PBL model assisted by worksheets (LKPD) proved more effective in improving student activity and learning outcomes in acid-base material and encouraging more student-centered learning.